Implementation of the Communication Function Against Embodiment of Superior HR in Era 5.0 in the Field of Economic Education - Dedi Hadian; Khaerul Syobar; Aan Hardiyana; Maulana Yusup (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to analyze the improvement of the quality of Human Resources is an absolute requirement so that the competence of the younger generation is able to compete inclusively in the era of society 5.0 and the industrial revolution 4.0 with special needs that cannot be separated from the influence of communication through technological sophistication and renewal. The communication function is a step in improving the quality of resources that are neatly integrated in the economic education of the younger generation. The method in this study uses a qualitative approach with descriptive research, by obtaining as complete information as possible through interviews, observation and documentation studies. This research was conducted in a higher education in Bandung. The findings of the research inform that the implementation of the communication function for the realization of superior HR in the 5.0 era in Economics education is 1) not maximally felt, so there is still a lot of need for guidance in the realization of superior HR in the 5.0 era, 2) the embodiment of superior HR in the 5.0 era has excellent programs from the field of education 3) improving the quality of entrepreneurs and superior human resource performance in the 5.0 era.